EVALUASI IMPLEMENTASI TES KEMAMPUAN AGAMA DALAM PENERIMAAN PESERTA DIDIK BARU - Mohammad Kanzul Fathon (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2023)
The writing of this article is motivated by the policy of the Blitar City government that implements a policy of carrying out a religious ability test for all sixth grade students who will continue to junior high school in the Blitar City area must take a religious ability test. The Blitar City Government considers it necessary to include a religious ability test to complete the quality requirements in the SMP PPDB process because it is considered a means of forming Indonesian human identity who has noble character and has faith and devotion to God Almighty. Blitar. The data in this study were obtained by collecting data through documentation and in-depth interviews with key informants related to the religious ability test policy that carried out by the Blitar City Education Office and Elementary Schools so that accurate and concrete data is obtained. The results of the study, show the process of implementing the policy of religious proficiency testing at the elementary school level in Blitar City in terms of resources, communication, disposition, and bureaucratic structure. Keywords: Policy implementation, religious ability, Junior High School